Development and Validation of a Flowsheet Simulation Model for Neptunium Extraction in an Advanced PUREX Process. Issue 4 (6th June 2016) - Chen, Hongyan; Taylor, Robin; Jobson, Megan; Woodhead, David; Masters, Andrew
ABSTRACT: An Advanced PUREX process has been developed for separation and recycling of neptunium from spent nuclear fuel. This work presents a new flowsheet simulation model for the extraction of neptunium using centrifugal contactors, where mass transfer is modeled using two-film theory and a linear driving force. Distribution coefficients and neptunium redox reactions are modeled using published models. Mass transfer between the organic and aqueous phases in the phase separation zone is shown to have a negligible effect. The model is applied to a previously tested flowsheet and its predictions are shown to be in good agreement with the experimental results.